2009
DOI: 10.1177/0143034309106948
|View full text |Cite
|
Sign up to set email alerts
|

Sticks and Stones Can Break My Bones, But How Can Pixels Hurt Me?

Abstract: Educators and the public alike are often perplexed with the enormous and evolving cyber mise en scène. Youth of the digital generation are interacting in ways our fore-mothers and fathers never imagined -using electronic communications that until 30 years ago never existed. This article reports on a study of cyber-bullying conducted with students in grades 6 through 9 in five schools in British Columbia, Canada. Our intent was to quantify computer and cellular phone usage; to seek information on the type, exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
187
3
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(211 citation statements)
references
References 5 publications
7
187
3
14
Order By: Relevance
“…They also found that students were more likely to report cyberbullying about another student than they were to report it when it happened to them. Cassidy et al (2009) supports that cyberbullying takes place among groups of friends. Ybarra and Mitchell (2004) discuss how when there is poor caregiver monitoring of online behavior the children are twice as likely to harass others online.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…They also found that students were more likely to report cyberbullying about another student than they were to report it when it happened to them. Cassidy et al (2009) supports that cyberbullying takes place among groups of friends. Ybarra and Mitchell (2004) discuss how when there is poor caregiver monitoring of online behavior the children are twice as likely to harass others online.…”
Section: Introductionmentioning
confidence: 78%
“…Of the youth who said they harassed someone online, 82% said that someone else had said mean or hurtful things about them online. Cassidy et al (2009) determined that young people want to dialogue about cyberbullying and suggest that schools need to provide opportunity for students to discuss cyberbullying, its impact and ways to prevent this behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Canadian study (Cassidy, Jackson, & Brown, 2009), which surveyed 365 students in grades 6, 7, 8 and 9 (ages 11-15 years) from three elementary and two secondary schools in a large metropolitan region of British Columbia, found that most students use the internet on a daily basis and that their most common vehicle for cyber-bullying was via chat rooms or over email.…”
Section: New Technologies and School Violencementioning
confidence: 99%